Instantaneous Effect of Insole on the Balance of Adolescents With Flat Foot and Pes Cavus - Ali Fattahi; Zahra Koreili; Mitra Ameli (Biyumikānīk-i varzishī)
Objective: The purpose of this study was to examine the instantaneous effect of insole on the balance of adolescents with flat foot and Pes Cavus. Methods: In this quasi-experimental study, 34 adolescents with flat foot and Pes Cavus (17 girls and 17 boys) in the age range of 11 to 14 years in Tehran were randomly selected and their balance performance in static and dynamic positions was examined before and after instantaneous using of insole. Data were analyzed using paired t-test and independent t-test. Results: Paired t-test results showed that the instantaneous effect of insole on dynamic balance is significant (P=0.00), but it had no significant effect on static balance (P=0.07). The results of independent t-test showed no significant difference between the two groups in terms of dynamic balance (P=0.99) and static balance (P=0.52) in Pre-test phase. There was no significant difference between the two groups in dynamic balance (P=0.25) and static balance (P=0.72) in Post-test phase, either. Conclusion: Using medical insole can improve the dynamic balance in adolescents with Pes Cavus and flat foot, but has no effect on their static balance.